Resumption of post-partum oestrous behaviour and associated plasma progesterone profiles in Menz ewes - Mukasa-Mugerwa, E.; Ezaz, Z. (Cambridge University Press, 1991)
Measures the duration of the post-partum anoestrus interval of fifty Ethiopian Menz ewes maintained on pasture grazing with uncontrolled mating; describes their associated blood progesterone patterns; and assesses their reproductive potential.